Pembelajaran Bahasa Inggris dalam Meningkatkan Sumber Daya Manusia (SDM) Pariwisata Masyarakat Lokal pada Objek Wisata Cengkeh Afo Kota Ternate - Halida Nuria; Nurfani Nurfani (Universitas Khairun, 2019)
Many native languages in Indonesia who interact with other codes shift, including Ternate language. this research is focused on the Ternate language shift to Tidore in Foramadiyahi village. The goal of this research is to describe the shifting of Ternate to Tidore language in Foramadiyahi village. This is a descriptive and qualitative research. Based on the analysis, there have some reason why that hapen in that place while that place is in Ternate island itself. Therefore, the language speaker’s regeneration is neither well performed nor sustainably constructed.Keywords: language shift, language attitude and preference, sociolinguistics